Hybrid poly(lactic-co-glycolic acid) nanoparticles: design and delivery prospectives. Issue 1 (January 2015) - Pandita, Deepti; Kumar, Sandeep; Lather, Viney
Highlights: PLGA-hybrid nanoparticles are emerging as a versatile drug delivery vehicle. Their tunable properties and surface characteristics offer therapeutic/diagnostic solutions. PLGA–lipid nanostructures are being enormously explored. Abstract : Poly(lactic-co-glycolic acid) (PLGA), a US Food and Drug Administration (FDA)-approved copolymer, has been exploited widely in the design of nanoparticles because it is biodegradable, biocompatible, protects the drug molecules from degradation, and aids in producing sustained and targeted delivery. However, certain constraints associated with PLGA nanoparticles, such as poor drug encapsulation, polymer degradation, and scale-up issues, have led to the development of emerging hybrid PLGA delivery systems. These hybrid nanoparticles are core–shell nanostructures comprising either a PLGA core or a PLGA shell combining multiple functionalities within one system and, thus, exhibiting the complementary characteristics of two different platforms used for the delivery of a wide range of therapeutics and imaging.